2017
DOI: 10.1590/s0102-865020170080000010
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of the short-term central venous catheter. A comparison of two techniques

Abstract: Fixation of the short-term central venous catheter. A comparison of two techniques 1Abstract Purpose: To compare the fixation of the central venous catheter (CVC) using two suture techniques. Methods: A clinical, analytical, interventional, longitudinal, prospective, controlled, singleblind and randomized study in adult, intensive care unit (ICU) patients. After admission and indication of CVC use, the patients were allocated to the Wing group (n = 35, catheter fixation with clamping wings and retainers) or Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…The additional suturing of the segmentation site has been recommended to avoid dislodgement [6], even though this approach has not been evaluated systematically. A recent clinical study demonstrated that a combination of “clamp only” plus “finger trap” was superior to “clamp only” plus “fixation of the segmentation site” with regards to dislodgement rates and catheter kinking [17]. Our data support the assumption that fixation of the segmentation site increases the dislodgement force.…”
Section: Discussionsupporting
confidence: 81%
“…The additional suturing of the segmentation site has been recommended to avoid dislodgement [6], even though this approach has not been evaluated systematically. A recent clinical study demonstrated that a combination of “clamp only” plus “finger trap” was superior to “clamp only” plus “fixation of the segmentation site” with regards to dislodgement rates and catheter kinking [17]. Our data support the assumption that fixation of the segmentation site increases the dislodgement force.…”
Section: Discussionsupporting
confidence: 81%
“…Studies originated in Europe (31; 49%) (31-61), North America (12; 19%) (8, 62-72), South America (5; 8%) (22,(73)(74)(75)(76), Oceania (6; 10%) (77-82), Asia (4; 6%) (83-86), and Middle East (5; 8%) (87-91). There were 24 RCTs (38%), 28 prospective (44%) and 11 retrospective studies (17%).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…complications per 1,000 catheter days(22,34,36,49,55,56,63,64,67,72,76,82,85). Due to lack of consistency in outcome definitions, some study outcomes were eligible including: catheter dysfunction(34), CRBSI(73), kinking(76), fixation failure(74,76), displacement(76), infection(22,56), exudate(74), catheter related infection(57)(58)(59), catheter infection (56), local reaction(74). (95% CI 3-12; 4 studies; 1,481 CVADs) and highest pooled IR 11.2 (0-22.9) per 1,000 catheter days (3 studies; 8,809 catheter days).…”
mentioning
confidence: 99%
“…Infraclavicular subclavian vein (SV) catheterization may sometimes be used for this purpose in cardiac surgery. As the catheter usually stays in place for more than a week, it causes patient discomfort (especially after internal jugular vein catheterization) [1][2][3]. In addition to routine internal jugular vein catheterization, SV catheterization is sometimes used at Farshchian Cardiovascular Hospital, Hamadan, Iran.…”
Section: Introductionmentioning
confidence: 99%